Analysis of Ergonomic Work Fatigue Limits on Performance and Productivity Improvement - Gempur Santoso (International Journal of Integrative Sciences, 2024)
In work, it should not be tiring. Thus, having good performance, resulting in optimal productivity. This paper discusses that through literature. Therefore, this writing is designed descriptively, namely an exposition. Data is taken from literature consisting of various opinions and research results, known as literature studies. The data collected includes fatigue, fatigue limits, performance, and productivity. Data analysis is carried out descriptively. Then, the conclusion of the data analysis is done inductively. Conclusions: 1) that the fatigue limit in work to prevent exhaustion includes: working for 8 hours per day or 40 hours per week; when working, using 35%-50% of maximum VO2; the maximum limit of energy usage during work is 5.0 kcal/minute to 5.2 kcal/minute; and working to have good strength so as not to easily tire when a group of muscle origins moves muscle insertions. 2) that working should be within the fatigue limit to maintain good performance, and ultimately, productivity increases optimally. Recommendations: workers should not easily tire during work, therefore, use and improve work equipment. Work equipment should be provided by the industry/company